Preventing family transmission of anxiety: Feasibility RCT of a brief intervention for parents. (25th March 2018) - Cartwright‐Hatton, Sam; Ewing, Donna; Dash, Suzanne; Hughes, Zoe; Thompson, Ellen J.; Hazell, Cassie M.; Field, Andy P.; Startup, Helen
Abstract : Objectives: Children of anxious parents are at high risk of anxiety disorders themselves. The evidence suggests that this is due to environmental rather than genetic factors. However, we currently do little to reduce this risk of transmission. There is evidence that supporting parenting in those with mental health difficulties can ameliorate this risk. Therefore, the objective of this study was to test the feasibility of a new one‐session, group‐based, preventive parenting intervention for parents with anxiety disorders. Design: Feasibility Randomized Controlled Trial. Methods: A total of 100 parents with anxiety disorders, recruited from adult mental health services in England (and child aged 3–9 years), were randomized to receive the new intervention (a 1‐day, group workshop), or to treatment as usual. Children's anxiety disorder and anxiety symptoms were assessed to 12 months by outcome assessors who were blind to group allocation. Exploratory analyses were conducted on an intention to treat basis, as far as possible. Results: A total of 51 participants were randomized to the intervention condition and 49 to the control condition (82% and 80% followed to 12 months, respectively). The attendance rate was 59%, and the intervention was highly acceptable to parents who received it. The RCT was feasible, and 12‐month follow‐up attrition rates were low. Children whose parents were in the control condition were 16.5% more likely to have an anxiety disorder at follow‐up than those in the intervention group. No adverse events were reported. Conclusions: An inexpensive, light‐touch, psycho‐educational intervention may be useful in breaking the intergenerational cycle of transmission of anxiety disorders. A substantive trial is warranted. Practitioner points: Anxiety disorders run in families, but we currently do little to help anxious parents to raise confident children. A brief group workshop was highly acceptable to such parents and was very inexpensive to run. Children of parents who took part in the brief intervention were 16.5% less likely to have an anxiety disorder, 1 year later, than children whose parents were in the control group. This was a feasibility study, and while it showed that both the intervention and the research were feasible, the study needs replicating with a much larger sample. Many parents faced barriers to attending the workshop, and future efforts should focus on widening accessibility. We were unable to obtain sufficient self‐report data from children, so the outcomes are based on parent report only.